ChemInform Abstract: Copper(I)—Y Zeolite Catalyzed N‐Sulfonylketenimine Mediated Annulation of Hydroxynaphthoquinones: Syntheses of Naphtho[2, 1‐b]furan‐2, 5‐diones and Benzo[de]chromene‐2, 6‐diones. Issue 46 (27th October 2016) - Ramanathan, Devenderan; Namitharan, Kayambu; Pitchumani, Kasi
Abstract: Photochemical properties as well as the anticarcinocenic activity of some products are examined.